INTERTEXTUALITY AND THE HEDGING SYSTEM OF THE FILIPINO ENGINEERING STUDENTS: PRACTICES AND PEDAGOGY - Melon-Galvez, Susana (UPI Press, 2017)
Communicators must have a ‘pact’; right idea, equals the ‘right words’. Although text is taken wholly to get to the meaning, every word contributes to the message sent for a powerful effect to the receiver. For language to work, participants must therefore be in full control of the words to be used. How these words are framed or intertextualized brings the hedging system of the ESP students. To achieve precision in ESP writing is not simply done by stringing words. To effectively communicate, there are underlying principles to apply to improve constant human interaction. In order to maintain such relationship in the technical world, each participant must not totally eradicate the ‘feeling’ to get across to the meaning. The study aimed at finding out the use of hedges and the effects of task types caused by framing of ideas and whether these hedges were significant to Filipino ESP writers. Common practices were identified as well as some pedagogical implications in the writing of technical discourses. Using introspection and contextual analysis, the researcher was able to analyze hedges varying from words, phrases, to clauses. The researcher found nonsensicality in intextualizing ESP texts and had no bearing on the hedging system of the ESP writers.